Pendampingan Pengolahan Biogas Limbah Kotoran Sapi pada Masyarakarat Peternak Kepulauan - Maulida, Yusni; Budiartiningsih, Rahmita; Hellyward, James; Harahap, Anwar Efendi; Juliantoni, Jepri; Arigi, Dylan Haikal; Mawaddah, Aidha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Based on data from Central Statistics Agency for 2022, the number of beef cattle in the Meranti Islands is 3,927 tail, 9 buffaloes and 7,985 goats. This very large livestock population is certain to produce large amounts of livestock manure because the cattle population is always directly proportional to the production of livestock manure. This assistance has a purpose aims to produce appropriate technology through the use of solid and liquid waste from livestock manure as a source of biogas. The method devotion is counseling and assistance regarding biogas originating from livestock manure in livestock groups in the Meranti Islands. The institution that will be a partner in biogas development technology activities is the Mantiasa Village independent cattle group, which is a non-productive livestock group. The community service parameters observed is the degree of acidity (pH). The results of the service obtained by the Mantiasa Village livestock group can utilize Biogas from livestock waste which is always available and can be distributed to 3-5 families, so that breeders and the community no longer use conventional gas for cooking. The use of biogas products by breeders and the community can save people's living costs because the price of conventional gas for cooking is high.